2010
DOI: 10.1038/ajg.2010.32
|View full text |Cite
|
Sign up to set email alerts
|

Novel Blood Biomarkers of Pancreatic Cancer–Associated Diabetes Mellitus Identified by Peripheral Blood–Based Gene Expression Profiles

Abstract: Our results indicate that the combination of VNN1 and MMP9 may be used as a novel blood biomarker panel for the discrimination of pancreatic cancer-associated diabetes from type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 36 publications
1
54
0
1
Order By: Relevance
“…Numerous genes were found to be differentially expressed on bioinformatic analysis of the gene expression profiles, consistent with former reports [16,17]. We then extracted secretory genes and did GO analysis.…”
Section: Discussionsupporting
confidence: 62%
“…Numerous genes were found to be differentially expressed on bioinformatic analysis of the gene expression profiles, consistent with former reports [16,17]. We then extracted secretory genes and did GO analysis.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, a recent study showed that the protein levels of renal vanin-1 increased in rats with streptozotocin-induced diabetic nephropathy, and urinary vanin-1 was detected in patients with diabetic nephropathy (Fugmann et al, 2011). Vanin-1 protein expression was detected in the pancreas of patients with pancreatic cancerassociated diabetes mellitus, but the Western blotting results for vanin-1 in serum were not available (Huang et al, 2010). Therefore, it is speculated that urinary vanin-1 might be of renal origin.…”
Section: Discussionmentioning
confidence: 99%
“…Using microarray analysis, Pfeffer et al (2004) identified connexin 26, a gap junction protein, as being highly overexpressed in PC patients with DM. Using similar methods, Huang et al (2010) identified two upregulated genes in 27 patients with PC-associated DM, vanin-1 and matrix metalloproteinase 9, that Endocrine-Related Cancer (2012) 19 F9-F26 www.endocrinology-journals.org F17 together showed the best correlation with the diagnosis. No large-scale studies have been reported yet regarding the sensitivity and specificity of these possible biomarkers.…”
Section: Diabetes As a Consequence (And Harbinger) Of Pc The Prevalenmentioning
confidence: 99%